Geographic tracing of cereals from South Tyrol (Italy) and neighboring regions via 87Sr/86Sr isotope analysis. (30th March 2023) - Bacher, Felix; Aguzzoni, Agnese; Chizzali, Samira; Pignotti, Emanuela; Puntscher, Hannes; Zignale, Pietro; Voto, Giulio; Tagliavini, Massimo; Tirler, Werner; Robatscher, Peter
Highlights: The grain 87 Sr/ 86 Sr ratios was highly correlated to that of the soil. The cereal species did not affect the 87 Sr/ 86 Sr ratios of the grain. The 87 Sr/ 86 Sr ratio in cereals was temporally stable. Significantly different 87 Sr/ 86 Sr ratios were found in areas with different geology. The Sr isotope ratio represents a robust marker for food traceability. Abstract: The protection and promotion of agricultural niche products can be supported by the application of analytical techniques able to link food to its territory. This study aimed at exploring the possibility to discriminate between cereal samples from South Tyrol (Italy) and the neighboring regions (Trentino, East Tyrol, and North Tyrol) by their 87 Sr/ 86 Sr ratios. Soil and grain (different species) samples were collected from around 100 fields in two sampling campaigns. No difference in the 87 Sr/ 86 Sr ratios among different cereal species (p < 0.05) was found when cultivated on the same field. A high correlation between 87 Sr/ 86 Sr ratios in cereal grains and soil samples was found, with results in line with the local geology characteristics. Cereal samples from South Tyrol showed relatively high 87 Sr/ 86 Sr values (0.716 – 0.721, mean 50%), separating them from the other regions investigated and many cereal production areas of global importance.